Problems in the organization and implementation of the teacher-education program of the Zamboanga Normal College - Camaongay, Mariano L. 1921- (1965)
The purpose of the study is to present an interpretation and case analysis of the first two years of the Zamboanga Normal College by showing its organizational structure and internal administration, the discovery and identification of problems connected with the organization and implementation of the teacher-education program, and the formulation and clarification of some basic guidelines for the implementation of the program from which a plan for sound college administration may be drawn. Specific cases to illustrate the problems encountered are presented to give a clear picture of the different situations involved.
Vita.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Teachers -- Education -- Philippines -- Zamboanga; Teachers -- Training of -- Philippines -- Zamboanga; Curriculum planning -- Philippines -- Zamboanga